Two Optimization Mechanisms to Improve the Isolation Property of Server Consolidation in Virtualized Multi-core Server - Kejiang Ye; Xiaohong Jiang; Deshi Ye; Dawei Huang (2010 IEEE 12th International Conference on High Performance Computing and Communications, 2010)
Virtualization brings many benefits such as improving system utilization and reducing cost through server consolidation. However, it also introduces isolation problem when running multiple virtual machine workloads in one physical platform. Additionally, with the advent of multi-core technology, more and more cores are built into one die in today's data center that will share and compete for the resource like cache. It's worthy to study the isolation of server consolidation in modern multi-core platform. However, to our knowledge there are few work done on the isolation property especially the fault isolation property when one of the virtual machine workloads is attacked in server consolidation. In this paper, we study the isolation property from performance perspective and provide two optimization methods to improve the isolation property. We first define the isolation property and quantify the performance isolation in consolidation and propose a VM-level optimization method. Then we study the fault isolation by introducing a misbehavior virtual machine in server consolidation scenario and propose a core-level cache-aware optimization method to improve the fault isolation. Experimental results show that our two optimization methods can effectively improve the performance isolation and fault isolation with 29.39% and 19.52% respectively. What's more, Oprofile/Xenoprof toolkits are used to find out the factors affecting isolation property from the hardware events level.